Growth and needle loss of spruce, Picea abies (L.) Karst., and pine, Pinus sylvestris L., in South Sweden during 1985-1990. Relations to soil acidification, nutrients and stand age; Tillvaext och barrfoerlust hos gran, Picea abies (L.) Karst., och tall, Pinus sylvestris L., i Skaane under aaren 1985-1990 - relation till markfoersurning, naeringsaemnen och bestaandsaalder - "Olsson, Anders [Laensstyrelsen i Kristianstad (Sweden)]" (Skaanes samraadsgrupp mot skogsskador, Kristianstad (Sweden), 1993)
During the last decades soils and forests of South Sweden has been exposed to acid rain and nitrogen deposition. Soil acidification affects several chemical variables in both soil and trees, and in this paper is described which chemical variables of soils and needles that are best correlated to and might explain the yearly growth and average needle loss of spruce and pine on 42 sample plots in Scania, southernmost Sweden. Variance analyses (PCA-factor analysis and stepwise regressions) indicate that growth is explained primarily by variables connected to soil acidity (pH explains 54%), needle loss (12%), and finally sand age (4%). Needle loss increases significantly with age, but is explained in spruce stands >30 years old primarily by pH in mor horizon (39%) and secondarily by the P-content in needles (14%), in total 53%. The P-content in needles is explained mostly by the exchangeable aluminium content in the mor horizon of the soil (30-59%). Variables coupled to the acid-base conditions of the soil (exchangeable acidity, exchangeable aluminium), exchangeable Ca, and base saturation are significantly correlated to growth and needle loss, and the pH-values of soil humus show usually the strongest correlations. The needle loss in spruce + pine stands is also correlated with the needle content of manganese, and in pine stand with the needle content of boron. No correlation exists between growth and nitrogen content of needles. The results support the hypotheses that growth and needle loss is connected with a continuous soil acidification that has bound up phosphorus, and that the combination with a high nitrogen deposition probably has made phosphorus a growth limiting element instead of nitrogen. 30 refs, 25 figs, tabs
Keywords: "09 BIOMASS FUELS"; "PINES"; "PLANT GROWTH"; "SPRUCES"; "SWEDEN"; "ACIDIFICATION"; "SOIL CHEMISTRY"; "SOILS"; "FORESTRY"; "PHOSPHORUS"; "NITROGEN"; "ALUMINIUM"; "MANGANESE"; "CALCIUM"; "BORON"; "PH VALUE"; "FIELD TESTS"; "NUTRIENTS"